Limitations in the 2D description of the electromagnetic waves propagation in thin dielectric and magnetic layers. Issue 12 (12th July 2018) - Radożycki, Tomasz; Bargieła, Piotr
Abstract: The propagation of electromagnetic waves trapped within dielectric and magnetic layers is considered. The description within the three-dimensional theory is compared to the simplified analysis in two dimensions. Two distinct media configurations of different topology are dealt with: a plane slab and a hollow cylinder. Choosing the appropriate values for the geometrical parameters (layer thickness, radius of the cylinder) and for the electromagnetic properties of the media one can trap exactly one mode corresponding to that obtained within the two-dimensional electromagnetism. However, the symmetry between electric and magnetic fields suggests, that the two versions of the simplified electromagnetism ought to be equally considered. Its usual form is incomplete to describe all modes. It is also found that there exists a domain of optimal values of parameters for which the 2 D model works relatively correctly. However, in the case of a cylindrical surface we observe several differences which may be attributed to the curvature of the layer, and which exclude the propagation of evanescent modes. The two-dimensional electrodynamics, whichever form is used, turns out still too poor to describe the so-called 'hybrid modes' excited in a real layer. The obtained results can be essential for proper description of the propagating waves within thin layers for which 3 D approach is not available due to mathematical complexity and reducing the layer to a lower dimensional structure seems the only possible option.